Herzog & de Meuron - Segni, tracce e latenze. Lavorare con la storia. Un progetto totale di un museo a Colmar - Calderoni, Alberto (Firenze Architettura, 2018)
The project of the Unterlinden Museum in the old city of Colmar (France), starts from the need to redefine the urban structure, to systematize and to expand the existing museum spaces. Trough this project Herzog & de Meuron reflect upon building intense, coherent and consistent atmospheres with new elements and spaces in the old context and considering how much the essence of the new architecture can be a driving force for the preservation of the old building.